Pruritus im Alter: eine interdisziplinäre Herausforderung - Weisshaar, Elke; Mettang, Thomas (Der Hautarzt, 2018)
Due to demographic change, especially in Western countries with increasing life expectancy and a continuously increasing number of elderly, chronic pruritus (CP) is more and more observed in clinical practice. CP in elderly may present with specific pruritic skin diseases, as chronic prurigo (nodular form) and can also occur in unaffected, normal looking skin. CP in elderly remains a challenge. Especially CP without any skin lesions is a major diagnostic and therapeutic challenge. Due to the increasing prevalence of malignant diseases in elderlies, paraneoplastic pruritus is also an important differential diagnosis. Treatment depends on the mobility of the patient which determines if and which topical agents can be used and if ultraviolet phototherapy can be administered. There are a number of topical and systemic medications, which must be selected according to existing comorbidities, possible drug interactions, and the patient’s compliance as well as possible side effects such as cognition and sedation. All this may hamper treatment of CP in elderly.
Gesehen am 01.07.2019